Flexible, Rapid Authoring of Goal-Orientated, Multi-Turn Dialogues Using the Task Completion Platform - Marin, Alex; Crook, Paul A.; Khan, Omar Zia; Radostev, Vasiliy; Aggarwal, Khushboo; Sarikaya, Ruhi (Interspeech 2016, 2016)
The Task Completion Platform (TCP) is a multi-domain, multimodal dialogue system that can host and execute large numbers of goal-orientated dialogue tasks. TCP is comprised of a task configuration language, TaskForm, and a task-independent dialogue runtime, allowing task definitions to be decoupled from the global dialogue policy used by the platform to execute the tasks. This separation enables scenario developers to rapidly develop new dialogue systems, by eliminating the need to reimplement the policy from scratch for each new task. In this paper, we introduce support for authoring tasks in a variety of dialogue styles, ranging from entirely flexible to fully system-initiative. This flexibility is enabled by a set of task-level policy override constructs, which augment or constrain the default platform-level policy to achieve the desired system behavior. We demonstrate the use of the TaskForm language to define complex, multi-turn tasks in a variety of domains and add different task-specific policy constructs to demonstrate the flexibility of the task authoring process.